(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2018)
Background: Globally, more than half of all TB cases are not detected. If they are not diagnosed and get treatment infection transmission may continue and patients suffer and may eventually die. Pulmonary TB either smear positive or negative is normally diagnosed by Ziehl-Neelsen stained sputum smear examination microscopy. Since the culture is the gold standard, evaluation of smear negative TB cases by this method is likely to detect more cases. Objectives: The objective of this study is to find out culture positivity among smear negative patients. Methods: All the three sputum samples reported negative by Ziehl-Neelsen microscopy from a total of 138 new TB suspected cases more than 15 years of age at NTC Laboratory. Nepal were cultured on Lowenstein-Jensen media. Tubes showing sufficient growth (culture positive) were recorded and all the culture positive results were informed to NTC. The culture positive samples were processed for DST on first line drugs using proportion method. Results: The culture positivity rate was 5.1% (7 of 138 cases) All the positive cultures were processed for DST on first line anti-TB drugs and none showed resistance of the total 138 suspected Tuberculosis patients, 94 (68.1%) were males and 44 were females (31.9%) with male: female ratio 1:047. The mean age of the total patients were 30.69. Nearly 42% of them belonged to 31-50 years. Mean age of the male patients was significantly higher than total of the female (p<.001). Conclusions: Seven smear negative cases among the total of 138 suspected TB patients attending NTC were culture positive. Similar study has to be done in other parts of the country.